Evaluation of the Sylimarin Effect on IL-10 and IL-17 Production in Blood Samples of Chronic HCV Infected Patients - Attaredelgosha, Pedram; Ravanshad, Mehrdad (Archives of Medical Laboratory Sciences, 2019)
Background: The use of herbal remedies, either in combination with conventional drugs or as an alternative, is accepted worldwide. Silymarin derived from Milk thistle has evidence-based therapeutic potency for wide spectrum of liver diseases. The current work aimed to study the immune-modulating activity of Silymarin in HCV-infected patients by measuring the effect of pure Silymarin solution on the production of IL-17 and IL-10. Materials and Methods: Nine HCV-1a infected patients and three healthy controls were entered in this study. The mean age of patients and healthy controls were 45.53 (± 10.21) and 39.9 (±10.88), respectively. The PBMCs were isolated, cultured in 96-well plate and incubated with Silymarin solution (5µg/ml) for 24 hours. The cells and cell culture supernatant of three groups including patients treated with Silymarin, non-treated patients, and healthy controls were then subjected to Real Time PCR and ELISA to measure the levels of inflammatory and non-inflammatory cytokines including IL-17 and IL-10, respectively. Statistical analysis was conducted using SPSS software version 20.0. Results: According to Real Time PCR and ELISA results, the level of IL-17 was significantly reduced in patients treated with Silymarin while the expression of IL-10 was remarkably increased in these patients. Conclusion: The results of this study approved the immunomodulatory properties of Silymarin in HCV-infected patients. Hepatoprotective, antiviral, as well as immunomodulatory properties of the Silymarin make it a potential therapeutic option in patients with chronic hepatitis C.